Putting principles for nutrition-sensitive agriculture and food systems in practice: Lessons learnt from field - Bayasgalanbat, Nomindelger (2019)
As part of the IFPRI Egypt Seminar in partnership with the National Nutrition Committee (ASRT affiliated): "100 million healthy lives: Scientific evidence on the double burden of malnutrition in Egypt"